Exploring discovery : the front door to your library's licensed and digitized content - Varnum, Kenneth J., 1967- (Facet Publishing, 2016)
The pace of change in recent decades has been dizzying. An index of books was a static item; discovery might require searching several places to find both the index and the item. Now the variety of materials managed and collected by individual librarys is expansive, and the concept of "discovery" can cover hundreds, thousands or even billions of items. Where is "discovery" going... and how will it change your life?